Phenomenology Of Using Instagram Close Friend Features For Self Disclosure Improvement - Lambok Hermanto Sihombing; Maria Paskalia Aninda (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
Social media basically has a function to share information related to user activities and convey information about themselves or called self-disclosures. However, users are not broadly and freely conveying something because of an attitude of vigilance so that there is limited space for movement that must be considered and needs to be considered. Social media that is currently in great demand is Instagram with various interesting features, one of which is the close friend feature that can be used to limit the user's space in providing information related to privacy. This study uses the theory of Human Communication proposed by Littlejohn (1996) as the main conceptual framework for a broader analysis of how the close friend feature influences users' self-disclosure using a descriptive qualitative approach. Overall, the results of interviews with five user informants of the close friend feature indicate that users want to create a sense of security, and limit their movement space so that users can control the situation in the sense that users know anyone who sees information about themselves intentionally and believes that close friends become proper space maintain privacy. Keywords: Instagram, Close Friend, Privacy, self-disclosures, Media.